2016
DOI: 10.1016/j.nucmedbio.2016.08.009
|View full text |Cite
|
Sign up to set email alerts
|

111In-labeled trastuzumab-modified gold nanoparticles are cytotoxic in vitro to HER2-positive breast cancer cells and arrest tumor growth in vivo in athymic mice after intratumoral injection

Abstract: A local radiation treatment for HER2-positive BC based on AuNP modified with trastuzumab and labeled with the Auger electron-emitter, In was developed and shown to arrest tumor growth with no normal tissue toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 28 publications
4
54
0
Order By: Relevance
“…Thus, the uptake of bioconjugated nanoparticles in cells with overexpressed receptors greatly increases. Unfortunately, the limitation of intravenously administrated NPs is their sequestration by the liver, lungs, and spleen, causing rapid elimination from the blood, radiation exposure of these organs and low tumor uptake [10].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the uptake of bioconjugated nanoparticles in cells with overexpressed receptors greatly increases. Unfortunately, the limitation of intravenously administrated NPs is their sequestration by the liver, lungs, and spleen, causing rapid elimination from the blood, radiation exposure of these organs and low tumor uptake [10].…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] Nanoparticle drugs have been exploited to circumvent the low bioavailability, rapid degradation and inactivation of drugs, and can rapidly enhance the permeability and retention (EPR) effect, and their ability to reduce the off-target toxicities of chemotherapeutics in tumors has been explored, leading to safe delivery systems and stable efficacy. [15][16][17][18] Recently, the use of UAloaded poly-D,L-lactic-co-glycolic acid nanoparticles (UA-NPs) as drug carrier was evaluated for differential tumor targeting effects in B16F10 melanoma cells. Smooth spherical nanoparticles of small size with relatively narrow size distribution ($154 nm) were produced through a single emulsication technique, and about 4% drug-loading efficiency and high encapsulation efficiency ($40%) were obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Table 4 summarizes a number of recent studies on HER2-targeted nanomedicine. [55][56][57][58][59] Although HER2 antibody is a targeting moiety commonly used for HER2+ cancer, other HER2 targeting ligands have also been studied. For instance, Ding et al used trastuzumab-mimetic peptide with promising results, and suggested that this may reduce the immunogenicity, production costs and technical efforts associated with the antibody.…”
Section: Latest Trend For the Development Of Nanomedicine-based Breasmentioning
confidence: 99%